Dynamics of Intra-guild Predation Model with Stage Structure in Prey - Hukmah Hukmah; Syamsuddin Toaha; Jeffry Kusuma (Jurnal Matematika, Statistika dan Komputasi, 2021)
The Intra-guild predation model is an interaction between three species where two of them compete and prey on each other for the same resource. This study considers the stage structure of prey on and combines Beddington-DeAngelis and Holling type I as functional responses in the model. Furthermore, the equilibrium point and stability of the model will be analyzed. The numerical result at the equilibrium point shows that the solution converging toward the equilibrium point so that the population is stable and will not become extinct with increasing time. In addition, the population tends to be stable when the density of prey is larger than the predator.